Perbandingan Antara Metode Discriminant Analysis Dan Logistic Regression Untuk Analisa Faktor-faktor Yang Mempengaruhi Prestasi Akademik Mahasiswa - Mercurius Broto Legowo (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
The purpose of this empirical study conducted to determine the factors influencing student academic performance in Perbanas Institute Jakarta. Multiple Discriminant Analysis and Regression Logistic as main statistical multivariate analysis method were used in this study. Results of the analysis will be determined that the Logistic Regression method is more accurate and superior as well as determine the factors that influence students' academic performance Perbanas Institute. Student Academic Performance in the case study students of Perbanas Institute, using the comparison between discriminant analysis method and regression logistic were influenced by factors duration of study, student motivation, student family environmental factors, and Quality of Learning, and E-Learning System. This comparative study reveals that the logistic regression method is much better and more accurate than the Discriminant Analysis method.